Determination of Total Phenolic Content, Total Flavonoid Content, Antioxidant Activities, and Soluble Sugars of Different Varieties of Banana Fruit Pulps Grown in Some Woredas in Bench Sheko and Sheka Zones, Southwest Ethiopia - Shisho Haile; Sintayehu Gashaw; Jemal Kassahun (Journal of Food Quality)
This study investigated bioactive materials and soluble sugar contents in banana fruit collected from local farmers. Banana fruit samples were collected from three potential plantation districts. Among ripening method, only the dried banana leaf wrapping technique resulted in the required ripening. Thus, analysis of parameters was conducted. Therefore, the dried banana fruit pulp was analyzed for phenols, flavonoids, antioxidants, free radical scavenging (FRS) activities, and soluble sugars. The obtained result showed the presence of significant differences between the analyzed banana fruit varieties and growing districts. Overall, the phenolic contents among the banana fruit pulp ranged from 36.28 to 45.34 GAE mg/100 g of banana fruit pulp, while the flavonoids ranged from 3.35 to 7.95 QE mg/100 g. Similarly, the antioxidant activity ranged from 12.09 to 19.56 AAE mg/100 g, while the free radical activity (DPPH) was 62.10%–94.80%. Also, the IC50 value ranged from 0.04 to 0.07. The analyzed soluble sugar contents ranged from 6.10 to 11.0 g/100 g. Giant cavendish varieties have highest total phenolic content (TPC), while Dwarf Cavendish verities have highest antioxidant activity. Banana variety affect TPC, FRS, and sucrose content, while place where banana grown affect only total flavonoid content (TFC) and FRS. TACs and sugar are strongly linked. However, TFC shows moderate negative correlations with both TACs and sugar, suggesting higher TFCs mean lower TACs and sugar. TFCs show borderline differences across districts, with Debub Bench appearing to have lower TFCs, but a nonsignificant trend for higher TACs and sugar. Obtained results agree with other previously reported values. Thus, the analyzed banana fruits have appreciable amount of bioactive compound and soluble sugars.